Thermophilic Solid-State Anaerobic Digestion of Corn Straw, Cattle Manure, and Vegetable Waste: Effect of Temperature, Total Solid Content, and C/N Ratio. (11th November 2020) - Su, Lianghu; Sun, Xu; Liu, Chenwei; Ji, Rongting; Zhen, Guangyin; Chen, Mei; Zhang, Longjiang
Abstract : Thermophilic solid-state anaerobic digestion (SS-AD) of agricultural wastes, i.e., corn straw, cattle manure, and vegetable waste, was carried out in this study. The effects of temperature (40-60°C), initial solid content (ISC, 17.5-32.5%), and C/N ratio (15-32 : 1) on biogas production were evaluated using a Box-Behnken experimental design (BBD) combined with response surface methodology (RSM). The results showed that optimization of process parameters is important to promote the SS-AD performance. All the factors, including interactive terms (except the ISC), were significant in the quadratic model for biogas production with SS-AD. Among the three operation parameters, the C/N ratio had the largest effect on biogas production, followed by temperature, and a maximum biogas yield of 241.4 mL gVS -1 could be achieved at 47.3°C, ISC = 24.81 %, and C / N = 22.35 . After 20 d of SS-AD, the microbial community structure under different conditions was characterized by high-throughput sequencing, showing that Firmicutes, Bacteroidetes, Chloroflexi, Synergistetes, and Proteobacteria dominated the bacterial community, and that Firmicutes had a competitive advantage over Bacteroidetes at elevated temperatures. The biogas production values and relative abundance of OPB54 and Bacteroidia after 20 d of SS-AD can be fitted well using a quadratic model, implying that OPB54 and Bacteroidia play important roles in the methanogenic metabolism for agricultural waste thermophilic SS-AD.